Rising Strong: Peruvian Women Entrepreneurs’ Journey through the COVID-19 Pandemic - (:unkn) unknown (IEEE, 2024)
This study explores the challenges faced by Peruvian women entrepreneurs during COVID-19 pandemic, their emotional responses, and coping mechanisms. Structured interviews with 51 women entrepreneurs were analysed using thematic analysis, framed by social...
Keywords: Mujeres emprendedoras; COVID-19